2019
DOI: 10.1093/ofid/ofz393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnosis and Prescribing Practices Between Virtual Visits and Office Visits for Adults Diagnosed With Sinusitis Within a Primary Care Network

Abstract: Background Many antibiotics prescribed in the outpatient setting result from upper respiratory tract infections (URTIs); however, these infections are often viral. Virtual visits have emerged as a popular alternative to office visits for URTIs and may be an important target for antimicrobial stewardship programs. Methods This retrospective cohort study evaluated adult patients diagnosed with sinusitis treated within a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 13 publications
1
71
0
1
Order By: Relevance
“…Most research has been conducted on data derived from synchronous virtual visits in American health care settings, where antibiotic prescription is historically higher [6], possibly due to a more market-controlled health care system with incentives for high patient satisfaction [7]. Consequently, there have been mixed results regarding antibiotic prescribing following virtual visits in various contexts [4,[8][9][10][11][12][13][14][15][16][17][18], with most studies focusing on urinary tract infections (UTIs) and upper respiratory infections. For example, depending on the health care provider, virtual visits for sinusitis have been associated with both higher [14] and lower [10,13] prescriptions rates compared with office visits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research has been conducted on data derived from synchronous virtual visits in American health care settings, where antibiotic prescription is historically higher [6], possibly due to a more market-controlled health care system with incentives for high patient satisfaction [7]. Consequently, there have been mixed results regarding antibiotic prescribing following virtual visits in various contexts [4,[8][9][10][11][12][13][14][15][16][17][18], with most studies focusing on urinary tract infections (UTIs) and upper respiratory infections. For example, depending on the health care provider, virtual visits for sinusitis have been associated with both higher [14] and lower [10,13] prescriptions rates compared with office visits.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there have been mixed results regarding antibiotic prescribing following virtual visits in various contexts [4,[8][9][10][11][12][13][14][15][16][17][18], with most studies focusing on urinary tract infections (UTIs) and upper respiratory infections. For example, depending on the health care provider, virtual visits for sinusitis have been associated with both higher [14] and lower [10,13] prescriptions rates compared with office visits. Comparisons to urgent care settings often demonstrate lower prescription rates for virtual visits [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In die Auswertung eingeschlossen wurden FĂ€lle mit typischen Symptomen einer Infektion der oberen Atemwege. Es konnte kein signifikanter Unterschied hinsichtlich der leitliniengerechten Behandlung, insbesondere der Verschreibung von Antibiotika, festgestellt werden [30].…”
Section: Nasenuntersuchungunclassified
“…One study showed that adult patients presenting with sinusitis, received a higher rate of guideline-concordant diagnosis and a lower prescription of antibiotics at virtual visits compared with in-o ce primary care visits. So, the virtual patients received more often an appropriate diagnosis of viral sinusitis, which implies a lower rate of antibiotic prescribing [27]. Other studies demonstrated no difference [28,29,30,31].…”
Section: Introductionmentioning
confidence: 97%
“…It is said that online doctors in Sweden are not as thorough as physicians in PHC in following STRAMA's guidelines and recommendations and therefore prescribe antibiotics more often [8,9]. However, there are studies indicating lower prescribing of antibiotics in remote consultations compared to face-to-face consultations [6,27]. One study showed that adult patients presenting with sinusitis, received a higher rate of guideline-concordant diagnosis and a lower prescription of antibiotics at virtual visits compared with in-o ce primary care visits.…”
Section: Introductionmentioning
confidence: 99%